Thoracolumbar and Lumbopelvic Spinal Alignment During the Barbell Back Squat: A Comparison Between Men and Women - Victor Bengtsson; Lars Berglund; Fredrik Öhberg; Ulrika Aasa (International Journal of Sports Physical Therapy)
# Background